Radioactive gaseous-aerosol releases from the WWR-M research reactor - Yu. M. Lobach; V. M. Shevel (Âderna Fìzika ta Energetika, 2023)
The radiation impact of the WWR-M research reactor is possible due to the release of radioactive substances into the environment, which are generated during both operation and decommissioning. One of the operator's responsibilities is to take measures to avoid or optimize the generation and management of radioactive waste to minimize the overall impact on the environment. Gaseous and airborne wastes are released into the environment through ventilation and air cleaning systems, which are essentials of the overall reactor design. The main method for preventing radioactive contamination spread to the environment is the combination of a well-designed ventilation system having thorough cleaning of the exhaust air. An analysis of the source terms of the gaseous-aerosol emissions, a description of the existing radiation control system and special ventilation system, and an analysis of the actual gaseous-aerosol emissions are presented. The total amount of gaseous-aerosol emissions during the planned reactor dismantling activity is estimated. The sufficiency and effectiveness of the existing system to ensure the required level of reactor safety are shown.